Studi Pengembangan Kelapa Sawit Rakyat di Provinsi Riau - Ahmad Rifai; Syaiful Hadi; Nurul Qomar (Jurnal Sagu, 2008)
The study aimed to analyze development of smallholder oil palm plantations in Riau, focusing on patterns of partnership between farmer and estate companies, financial intitutions, marketing agents, and industries, and analyzed profit margin and farmer incomecontribution to household income. Data had been collected by household survey and indepth interviews, and analyzed using a descriptive-comparative method. The study identified that smallholder oil palm plantations were developed by finance scheme of Nucleus Estate Smallholder (NES), KKPA (Kreedit Koperasi Primer untuk Anggota), and pure self finance. According to the poverty criteriaby Sayogyo, most of the oil palm farmers are not in poor category. The productivity of pure self finance smallholder plantation is 15.5% to 44.0% from the research-based palm oil standart productivity, while smallholder plantations by NES and KKPA have 61,3% to 83,8% and 39,7% to 70,6% of the standart, respectively. It is due to diferences in seed used and agricultural technology applied. Marketing of fresh fruit bunches in smallholder plantations by NES and KKPA integrated with nucleus estate or company, while marketing by pure self finance smallholder plantations used intermediate sellers.